2009
DOI: 10.1111/j.1467-8500.2008.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Compliance Burden of Non‐profit Organisations: Cutting Red Tape

Abstract: Australian governments now rely on the non-profit sector to provide essential services. Yet, anecdotally, the compliance burden imposed by governments consumes scarce service delivery resources. This study quantifies the cost of government generated paperwork for Queensland non-profit organisations. Fourteen non-profits kept logs to record government paperwork over 12 months. The non-profits also provided their experiences of government paperwork and in particular grant submission and reporting processes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…In recent years there has been considerable research on how not‐for‐profit organisations have engaged with government when they are contracted to deliver government programs (Considine ; Domberger and Hall ; Flack and Ryan ; Butcher ; McGregor‐Lowndes and Ryan ; Spall and Zetlin ; Rogers ). Some commentators, in Australia and elsewhere, have suggested that not‐for‐profit organisations will need to re‐examine their own structures in the light of possible conflict between their obligations to funders and their mission (McCluskey ; Rogers ).…”
mentioning
confidence: 99%
“…In recent years there has been considerable research on how not‐for‐profit organisations have engaged with government when they are contracted to deliver government programs (Considine ; Domberger and Hall ; Flack and Ryan ; Butcher ; McGregor‐Lowndes and Ryan ; Spall and Zetlin ; Rogers ). Some commentators, in Australia and elsewhere, have suggested that not‐for‐profit organisations will need to re‐examine their own structures in the light of possible conflict between their obligations to funders and their mission (McCluskey ; Rogers ).…”
mentioning
confidence: 99%
“…Debates in the United Kingdom often take the form of a contest between providers and tenants' groups, each seeking to influence the regulator (see Cave 2007). 17 McGregor-Lowndes & Ryan (2009) note that organisations face an additional burden through supporting research on red tape. This could also be viewed as ritualistic if the burdens are not reduced.…”
Section: Resultsmentioning
confidence: 99%
“…As businesses become more successful over time and their turnover grow, owners tend to favour more complex business structures, particularly incorporation, to minimise risk and tax. This can increase both tax and non-tax compliance costs (McGregor-Lowndes & Ryan, 2009). Hence, the study assumes that business age influences on tax compliance costs.…”
Section: Business Agementioning
confidence: 99%